Bálano - Rojas Rebolledo, Eduardo, 1970- (Letras mexicanas., 2012)
Through the years, said Günter von Gropius, more than once have I felt certain feelings of anxiety, of a silent melancholy. Even though the motive may look foolish, tackiness very own of young women, it has always been the same: take at fault the complexity of a friend. That shortage is the way of Bálano, a novel by Eduardo Rojas Rebolledo where memory takes a lead role. Starting from the narrator's own memories, full of humor and melancholy, they outline what forms a friendship filled with sexual adventures, jilted lovers and jealousy, intrigue, painful affairs and death.